Adherigaun Narratives and Subaltern Myth Making in Maidaro - Chalise, Keshav Raj (Janapriya Journal of Interdisciplinary Studies, 2020)
The theory of subaltern studies, as the postcolonial way of analyzing and understanding literature and social relations, examines the context of the marginal ideologies, socio-political or literary. The basic value of subaltern philosophy, therefore, is the marginal case of social and political castration however it also includes the issues of domination, marginalization and discrimination caused by already established cultural politics of the society with social and economic diversity. The cultural politics keeps certain group of people under the marginal domain in the process of mythmaking. The society and social values do not accept these groups existing in the cultural politics, but still exploit them, their labour, work and ability in the name of their power as cultural power. Recently, such myths have been on the way to break down as the result of subaltern consciousness. With this sense of cultural politics of mythmaking, this study examines on how social and cultural narratives have raised the subaltern issues in Bhupeen’s novel Maidaro. The aspiration of this research is to unearth the subaltern narratives of the society depicted in the novel and to find out on how these narratives have become the central factors to dominate and overshadow certain group of people in the name of culture.